2008
DOI: 10.4049/jimmunol.180.11.7480
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differences in Bone Marrow-Derived Lymphoid Lineages Control Susceptibility to Experimental Autoimmune Myocarditis

Abstract: Bone marrow (BM) transplantation has been used to study the cellular basis of genetic control of autoimmune diseases, but conclusions remain elusive due to the contradictory findings in different animal models. In the current study, we found that BM cells from myocarditis-susceptible A.SW mice can render irradiated, myocarditis-resistant B10.S recipient mice susceptible to myosin-induced myocarditis, indicating that hematopoietic cells express the genetic differences controlling susceptibility to autoimmune my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…We have extended here our previous findings showing that genetic susceptibility to EAM was mediated by T lymphocytes [17]. We showed that intrinsic differences in the frequency of CD4 + T cells and Tregs and their ability to receive cytokine instruction to differentiate towards specific T helper subtypes could represent a factor in the susceptibility of A.SW and B10.S mice to autoimmune myocarditis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We have extended here our previous findings showing that genetic susceptibility to EAM was mediated by T lymphocytes [17]. We showed that intrinsic differences in the frequency of CD4 + T cells and Tregs and their ability to receive cytokine instruction to differentiate towards specific T helper subtypes could represent a factor in the susceptibility of A.SW and B10.S mice to autoimmune myocarditis.…”
Section: Discussionsupporting
confidence: 80%
“…Using bone marrow chimeric mice, we have shown previously that genetic susceptibility of myocarditis is controlled by donor‐derived haematopoietic cells, and that T and B lymphocytes were indispensable for transferring the susceptible phenotype to disease‐resistant recipients [17]. To continue with this line of research, we performed a comprehensive flow cytometric analysis of splenocytes from naive A.SW and B10.S mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α-MyHC/CFA immunization induces myocarditis in susceptible strains only. Mice on BALB/c, A/J or A.SW background are susceptible to EAM, while mice on C57BL/6 background are resistant (134, 159161). From a practical point of view, the resistance to EAM of widely-used C57BL/6 strain limits use of numerous transgenic models without the need for back-crossing onto the susceptible background.…”
Section: Mouse Models Of Experimental Myocarditismentioning
confidence: 99%
“…Bone marrow (BM) transplantation is used to investigate the contribution of haematopoietic versus non‐haematopoietic cell lineages in autoimmune disease development [14,15]. In this study, our aim was to investigate whether BM‐derived cells play a role in the profound improvement of renal disease and survival in Fli‐1 +/− MRL/ lpr mice.…”
Section: Introductionmentioning
confidence: 99%